Desafios enfrentados pelos técnicos administrativos do ensino superior no trabalho remoto emergencial e possíveis contribuições para o pós-pandemia - Silva, Marcos Alexandre Ferreira de Lima e (2023)
This research was developed within the scope of the Graduate Program in Public Policies and Educational Management, through actions developed by the study and research group DOCEFORM, which is a group of students from different areas who collaborate with each other in the research and development of studies. The research proposes to understand the policies and educational management in the educational context of higher education, specifically the management of the work of professionals who work in administrative activities called administrative technicians (TAs) in a Community Institution of Higher Education in Vale do Rio Pardo (IEs), focusing on the possibilities of implementing distance work for TAs, after the period of the COVID-19 pandemic. As an objective, we seek to understand the challenges of the TAs of a Private Community Higher Education Institution during the pandemic period, in order to answer how this work carried out during this time can contribute to new forms of management in Higher Education Institutions, bringing research questions on: 1) how the work of TAs was developed during the period of emergency remote work, 2) what training demands emerge from the work context of TAs during the pandemic period, 3) how the resources made available to TAs, during the pandemic, conditioned the development of work in the different sectors of the Institution and, finally, 4) how the pandemic period limited or enabled the advancement of sustainable practices in the work management of TAs. The absence of academic works that focus on these issues, especially for administrative work in educational institutions, justifies the imminent need for research on the subject. For the methodology, a qualitative approach was used, developed in the administrative sectors of the University of Santa Cruz do Sul - UNISC, which is a Private Community Institution of Higher Education in the Vale do Rio Pardo (IEs), using the discourse of collaborators, chosen according to their functions, which bring interface with the study. Therefore, the sources of information were 11 administrative technicians from the undergraduate course secretariats, and, to collect information, we propose structured interviews with qualitative analysis of the research subjects' responses. As main results, we obtained the recurrence of the speech of the administrative technicians interviewed about the beginning of the remote work period being complicated, difficult and distressing. They also talked about the fact that, during this period, they had to adapt their spaces to be able to perform their functions, and, after having done this, with their own investment, they considered it possible to work from home. The intention, based on the analyses, is to have subsidy to propose a pilot project of a committee to support the management of the hybrid work of ATs, as a product, and this multidisciplinary group and from several key sectors will be responsible, for example, for: identifying profiles of subjects who better adhere to the reality of remote work, provide technological tools for the proper performance of functions in locations outside the Institution, psychologically support employees on adverse issues that may arise with this different way of working, provide financial benefits for the acquisition of items and/or conditions of connections to perform their functions properly. These are just some of the main attributions of this new sector as a product of this research.